The Interplay Between Inflammation and Oxidative Stress in Carcinogenesis - Nowsheen, S.; Aziz, K.; B. Kryston, T.; F. Ferguson, N.; Georgakilas, A. (Current Molecular Medicine, 2012)
Emerging data suggest that primary dysfunction in the tumor microenvironment is crucial for carcinogenesis. These recent findings make a compelling case for targeting the milieu for cancer chemoprevention as well as therapy. The stroma is an integral part of its physiology, and functionally, one cannot totally dissociate the tumor surrounding from the tumor cells. A thorough understanding of the tumor and stroma will aid us in developing new treatment targets. In this review, we shed light at the key aspects of the carcinogenic process and how oxidative stress and inflammation contribute to this process. We dissect the connection between metastasis and oxidative stress and focus on the key players in the tumor microenvironment that leads to inflammation, oxidative stress and DNA damage. Moreover, we consider the role of inflammation in disease, specifically cancer and metastasis. Finally, we discuss the potential applications in prognosis and cancer treatment.
Keywords: inflammation